The correlation of iodine concentration in urine with muscle mass and reaction speed of young adults - Stjepan Ištvanić; Ivan Dusper; Tomislav Ištvanić; Vedran Farkaš; Ines Banjari; Tatjana Bačun (Medicinski glasnik, 2025)
Aim: To examine dietary iodine intake and urinary iodine concentration in young adults, as well as the relationship between iodine concentration in urine and muscle mass and speed of muscle reaction. Methods: Seventy euthyroid participants between the ages of 18 and 24 participated, 35 (50%) male and 35 (50%) female. The participants were young adults who live, study and work in the region of Osijek, Osijek-Baranja County, Croatia. Exclusion criteria were diagnosed thyroid disease and iodine metabolism disorder. Spot urine samples were analysed, dietary iodine intake was assessed, muscle mass and reaction speed were measured. Results: The median concentration of iodine in urine was 120.77 ?g/L, and the estimated iodine intake was 624.66 ?g. The median muscle mass was 32.55%, and the median speed of muscle reaction 274.5 ms. A significant, negative and weak correlation between iodine concentration in urine and speed of muscle reaction was observed (Rho = -0.289). Other associations of urine iodine concentration and muscle mass percentage, muscle tissue and reaction speed were not significant Conclusion: The estimated dietary iodine intake was higher than the reference values of the World Health Organization. The urinary iodine concentration was within the reference values. Urinary iodine concentration was not related to muscle mass. Urinary iodine concentration in urine was significantly, negatively and weakly related to reaction speed.
Keywords: diet surveys; population health; thyroid hormones